Pengaruh Jumlah Ruas Cabang Terhadap Pertumbuhan Setek Bambu Hitam (Gigantochloa Atroviolacea) - Wenty Irvantia; Indriyanto Indriyanto; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Black bamboo (Gigantochloa atroviolacea) is one of the famous bamboo species used, because it has many functions. The effort to maintain bamboo population is by cultivation. Generative cultivation of bamboo is difficult, so that vegetative cultivation by branch cuttings is carried. The aim of this research were to know the effect of number of internodes on black bamboo branch cuttings and the best influence on percentage of life and growth. The experiment used Completely Randomized Design (CRD) with 3 treatment sand 5 replications. The treatment were number of black bamboo branch, which were 2, 3,and 4 internodes. Eachbranchesplantedin polybag had filledwith top soil.The growth variables that measured were the percentage of life, number of shoots, length of shoot, diameter of shoot, number of leaves and length of root. The results showed that the number of black bamboo branch internodes influenced on length of shoot and number of leaves. Black bamboo branch with 4 internodes was the best result to growth of black bamboo branch cuttings because of highest value on length of shoot (3.84 cm) and number of leaves (4.90 sheet). Keywords: black bamboo, branch cuttings, number of internodes